Cortical reactivity and effective connectivity during REM sleep in humans - Massimini, M (2010)
We recorded the electroencephalographic (EEG) responses evoked by transcranial magnetic stimulation (TMS) during the first rapid eye movement (REM) sleep episode of the night and we compared them with the responses obtained during previous wakefulness and NREM sleep. Confirming previous findings, upon falling into NREM sleep, cortical activations became more local and stereotypical, indicating a significant impairment of the intracortical dialogue. During REM sleep, a state in which subjects regain consciousness but are almost paralyzed, TMS triggered more widespread and differentiated patterns of cortical activation, that were similar to the ones observed in wakefulness. Similarly, TMS/hd-EEG may be used to probe the internal dialogue of the thalamocortical system in brain injured patients that are unable to move and communicate.